RI 3404 The Pegmatites At Tinton, S. Dak. - General Statement (88bf1f31-0bbd-4012-9b9a-b0db19713349) - Frank L. Hess (The National Institute for Occupational Safety and Health (NIOSH), 1938)
In 1876 cassiterite was identified in the placer gold from the northern Black Hills, and such a mixture could have come only from Nigger Hill or one of the streams draining the hill, because in no other part of the northern hills have cassiterite and gold been found together. Nigger Hill is in western Lawrence County, South Dakota, and on it is the little camp of Tinton. The Wyoming line runs along the west side of the hill and crosses the ridge which is the hill's continuation about miles north-northwest of Tinton.